THE USE OF SOCIAL MEDIA IN LEARNING ENGLISH: “STUDENTS’ PERCEPTION” - Halawa, Fitriyani (Universitas Nias Raya, 2024)
This study deals with how students' perceptions of the use of social media in learning English. The purpose is to describe students' perceptions the use of social media in learning English. The design of di this research is qualitative research design. The data source is fifth English semester students of Nias Raya University. This study used an unstructured questionnaire with 32 participants. The result of the study is the social media platforms that were often used by them were Youtube, Instagram, Tiktok and Facebook. Those social media platforms provided lots of previous English material to be learned and possibly will provide many new things. Learning through social media can strengthen independent learning, students do not find any obstacles in using social media to learn English, social media provided fun learning for students, using social media increases in-depth knowledge for students, learning using social media has a positive impact on every positive impact of every learning accessed. It is concluded that students' perceptions of the use of social media make them fun in learning English by using this social media. The students can learn freely and enjoyable and the students can learn without pressure. The students happy to learn by using the social media. Learning from social media, it can be lead students to learn not only in their class, but anywhere. And Its make their knowledge and motivation increase. It is suggested that the results of this study can serve as a reference for future readers or researchers.